(untitled) (International Journal of Food and Nutritional Sciences, 2022)
There are several COVID-19 outbreak models for predictions which are being officially used all over the world to help the public for informed decisions and take the right safety measures in advanced. This paper describes the analysis of Prediction of Covid 19, with the help of various applications of data science like regression analysis and the time series Forecasting. In Regression there are two different models 1. Linear and 2. Polynomial. These two-regression model evaluation is done by R squared score function and error values function. This paper deals with the data set “Covid 19 dataset for India”. Regression model will result in confirmed, recovered and death cases. Forecasting will be for future trend of these cases, for this model author used forecasting model of tableau.